The usefulness of the FlowerBasket for endoscopic extraction of common bile duct stones with a diameter less than 1 cm - HIRAI, Masaaki; SANO, Hitoshi; ITOH, Makoto; AKITA, Shinji; GOTOH, Kazuo; MIYABE, Katsuyuki; OKAYAMA, Yasutaka; HAYASHI, Kazuki; UENO, Koichiro; NAKAZAWA, Takahiro; NAITO, Itaru; KITAJIMA, Yasuhiro; et al. (Tando, 2005)
In this study, we clinically evaluated the usefulness of the FlowerBasket for endoscopic extraction of common bile duct stones with a diameter less than 1 cm after EST. The subjects were 105patients with choledocholithiasis. As many stones as possible were extracted using FlowerBasket or a conventional 4-wire basket, and a further extraction was performed using a balloon catheter. To examine whether stones can be further extracted using the FlowerBasket, additional extraction was performed in some patients after extraction using the conventional 4-wire basket. Further extraction of stones was impossible using the 4-wire basket in 36% of the 61 patients, using the FlowerBasket in 63% of the 27 patients. The difference is significantly better in the FlowerBasket. Additional extraction of stones using the FlowerBasket was possible in 71% of the 17 patients. The FlowerBasket was a useful device for the accurate and rapid endoscopic extraction of common bile duct stones with a diameter of less than 1 cm after EST.